Accuracy of Dental Age in Nonadults: A Comparison of Two Methods for Age Estimation Using Radiographs of Developing Teeth1. Issue 5 (2nd February 2017) - Santana, Sierra A.; Bethard, Jonathan D.; Moore, Tara L.
Abstract: This research tests the accuracy of two methods for age estimation, Cameriere's European formula and AlQahtani's London Atlas, on a multi‐population American sample. Digitized radiographs of 360 European American, Hispanic, and American Indian children aged 6–17 years were analyzed. The accuracy of these methods was assessed using the mean and absolute mean difference of the residuals. Results indicate that Cameriere's European formula underestimated age for both sexes, with a mean difference of −1.19 years for girls and −1.32 years for boys, prompting the first author to create an American‐specific formula. The London Atlas underestimated age with a mean difference of −0.18 years for girls and −0.16 years for boys. Sex and ancestry had no significant affect on accuracy. The results indicate that both methods can be used for age estimation in an American population.